Handbook of indigenous fermented foods - Steinkraus, Keith H. 1918- (Microbiology series, 1995)
Covers information on indigenous fermented foods of the world, classifying fermentation according to type. This book provides data on the antiquity and role of fermented foods in human life, fermentations involving an alkaline reaction, tempe and meat substitutes, amazake and kombucha, and more